TRAINING HALAL SLAUGHTERERS IN SAMARINDA ON KNIFE SHARPENING WITH WHETSTONE AND SHARPENING STEEL - Wibowo, Ari; Suhardi, Suhardi; Ismanto, Arif; Ibrahim, Ibrahim; Aprylasari, Dede; Harris, Muhammad Ichsan; Daru, Taufan Purwokusumaning; Manullang, Julinda Romaulli (CV. Alina, 2024)
Slaughtering animals is a crucial stage in the food production chain, especially for Halal meat products that adhere to animal welfare standards. Proper knife sharpening techniques are essential in minimizing pain and stress for animals during the slaughtering process. This study reports on a training program in knife sharpening techniques using a combination of whetstones and sharpening steel conducted in Samarinda. The training involved Halal slaughterers from various mosques and markets in the Sambutan District of Samarinda. The method aimed to enhance the participants' skills in optimal knife sharpening, forming a blade edge that meets the animal welfare-based meat-cutting industry standards. The training results indicated that 75% of participants successfully applied the sharpening techniques that were taught, producing convex-shaped blade edges that were more efficient in the slaughtering process. This success positively impacted the implementation of animal welfare standards and the quality of the resulting meat. In conclusion, the training effectively improved Halal slaughterers' skills and significantly impacted the implementation of animal welfare standards in Samarinda. Support from the Samarinda City Food Security and Agriculture Office, the Animal Husbandry Department of Mulawarman University, and the Halal Slaughtering Da'wah Organization of Samarinda City played a crucial role in the success of this training.